2014
DOI: 10.1002/job.1958
|View full text |Cite
|
Sign up to set email alerts
|

It is time for justice: How time changes what we know about justice judgments and justice effects

Abstract: International audienceOrganizational justice is an important determinant of workplace attitudes, decisions, and behaviors. However, understanding workplace fairness requires not only examining what happens but also when it happens, in terms of justice events, perceptions, and reactions. We organize and discuss findings from 194 justice articles with temporal aspects, selected from over a thousand empirical justice articles. By examining temporal aspects, our findings enrich and sometimes challenge the answers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(60 citation statements)
references
References 200 publications
2
57
0
1
Order By: Relevance
“…For long spells (longer than three days), a physician's examination and a medical certificate are required. Maternity leaves and absences due to caring for a sick child are not included as sickness absences [1]. Information regarding the participants' sickness absences in this study was obtained from employers' registers between January 1, 2005 andDecember 31, 2006.…”
Section: Methodsmentioning
confidence: 99%
“…For long spells (longer than three days), a physician's examination and a medical certificate are required. Maternity leaves and absences due to caring for a sick child are not included as sickness absences [1]. Information regarding the participants' sickness absences in this study was obtained from employers' registers between January 1, 2005 andDecember 31, 2006.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, justice, social exchange, and time are theoretically intertwined in ongoing interactions of mutual obligation (Cropanzano & Mitchell, 2005;Fortin, Cojuharenco, Patient, & German, 2014). For example, in his seminal writing, Blau emphasized how "exchange…involves favors that create diffuse future obligations, not precisely specified ones " (1964: 93).…”
Section: Reciprocitymentioning
confidence: 99%
“…Gleibs et al (2008) found that procedural fairness perceptions had a positive relationship with post-merger identification over time. As Fortin, Cojuharenco, Patient and German (2014) emphasise, justice perceptions evolve over time; therefore, the knock-on effect of these perceptions should also vary across time. In an M&A context, employees' experiences across a period of organizational integration tend to involve a significant period of organizational change.…”
Section: Change In Perceived Justicementioning
confidence: 99%